Structural classification as a preservation means of Malaysian folktales - Harun, Harryizman; Jamaludin, Zulikha (2016)
Malaysian folktales are one of the intangible cultural heritages that reflect and carry the lineage of the past generations to the present. It deserves to be preserved systematically but thus far; it is found such effort is scarce if not lacking in this country.Therefore, a study is conducted to preserve such valuable heritage through structural classification of the folktales.To achieve such classification, embedded narrative structures of the folktales are sought and utilized.Additionally, as a method to guide the analysis to excavate the narrative structures, 31 functions of folktale’s morphology are adapted. To that end, this article presents the Malaysian folktale collected and also the finding of the analysis implemented on the collected folktales which are the sequences of function that eventually form the structural classification.